Symbol of Democratic Leardership in the Film "Tepatilah Janji Director Garin Nugroho" - Nurul Fadhillah; Dina Nurmalisa (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to describe the symbols of democratic leadership based on Roland Barthes' semiotic theory contained in the film Tepatilah Janji directed by Garin Nugroho. This film contains symbols of leadership during the period of political democracy or the regional head election period. The method used in this study is qualitative research. Research that is able to describe the meaning of denotation, connotation, and myth based on Roland Barthes' semiotic theory. The data source for this study is through direct observation by watching the film Tepatilah Janji on the Youtube application on the KPU RI account. While the data for this study is through image clips in the dialogue and scenes of the film. The data collection technique is with the stages of observation, documentation, and literature study. While the data analysis technique is by carrying out three stages of meaning, namely denotation, connotation, and myth. The analysis of this study is able to analyze the meaning, signs and symbols contained in the scenes and dialogues of the film. Researchers have found 3 symbols of democratic leadership, including symbols of abuse of office or authority, symbols of agreements with parties, and symbols of open debate. These symbols show scenes in the events of prospective leaders who are trying to maintain power and compete in the period of promised leadership or the campaign period. In addition, there are candidates for leaders who are ambitious in campaigning. He takes political actions that are not appropriate according to political regulations. These actions indicate the existence of symbols of political democratic leadership. Therefore, researchers will reveal the symbols of democratic leadership using Roland Barthes' semiotic theory.